Effects of α2A Adrenoceptors on Norepinephrine Secretion from the Locus Coeruleus during Chronic Stress-Induced Depression - Wang, Bin; Wang, Ying; Wu, Qiong; Huang, Hong-ping; Li, Shao (Frontiers in Neuroscience, 2017)
Chronic stressors can often lead to the development of psychological disorders, such as depression and anxiety. The locus coeruleus (LC) is a stress sensitive brain region located in the pons, with noradrenergic neurons that project to the hypothalamus, especially the paraventricular nucleus (PVN) of the hypothalamus. The purpose of this paper is to better understand how alpha 2A-adrenoceptors (α2A-ARs) and LC-hypothalamus noradrenergic system participate in the pathophysiological mechanism of depression. In vivo norepinephrine (NE) release in the PVN triggered by electrical stimulation in the LC was detected with carbon fiber electrode in depression model rats induced by chronic unpredictable mild stress (CUMS). Also, the extracellular level of NE in the PVN was measured by microdialysis in vivo without any stimulation of LC. The alpha 2-adrenoceptor (α2-AR) antagonist yohimbine and α2A-ARs antagonist BRL-44408 maleate were systemically administered to rats to determine the effects of α2A-ARs on NE release in the PVN. The peak value of elicited NE release signals in the PVN induced by electrical stimulation in the LC in the CUMS rats were lower than that in the control rats. The extracellular levels of NE in the PVN of the CUMS rats were significantly less than that of the control rats. Intraperitoneal injection of yohimbine or BRL-44408 maleate significantly potentiated NE release in the PVN of the CUMS rats. The CUMS significantly increased protein expression levels of α2A-AR in the hypothalamus, and BRL-44408 maleate significantly reversed the increase of α2A-AR protein expression levels in the CUMS rats. Our results suggest that CUMS could significantly facilitate the effect of α2-adrenoceptor-mediated presynaptic inhibition and decrease the release of NE in the PVN from LC. Blockade of the inhibitory action of excessive α2A-adrenergic receptor in the CUMS rats could increase the level of NE in the PVN, which is effective in the treatment of depressive disorders.